Development of The Website-Based Animated Video “SAMARA” on Surah Al-A'la in Islamic Religious Education Learning for 6th Grade Elementary School - Mukhoerrunnissa, Thania Kayla; Luminary, Hilwa Tiara; Nita, Nita; Wahyuni, Cintia Ira; Aeni, Ani Nur (Jurnal Inovasi Pendidikan Dasar, 2025)
The teaching of Islamic Religious Education (PAI) in elementary schools faces particular challenges, one of which is the low enthusiasm of students in understanding religious material, including Surah Al-A’la. Conventional teaching methods and the limited use of innovative media are the main factors affecting students’ interest and comprehension. Therefore, it is necessary to develop more interactive and engaging learning media. This study aims to develop the "SAMARA" animated video as a digital-based learning medium that is expected to increase students’ motivation and understanding of Surah Al-A’la. The research method used is Design and Development (D&D) with the ADDIE model approach (Analysis, Design, Development, Implementation, and Evaluation). The results show that the "SAMARA" animated video received a score of 97.5% from material experts and 100% from media experts, and contributed significantly to improving students’ learning enthusiasm.